2005
DOI: 10.3201/eid1107.040957
|View full text |Cite
|
Sign up to set email alerts
|

Primate-to-Human Retroviral Transmission in Asia

Abstract: We describe the first reported transmission to a human of simian foamy virus (SFV) from a free-ranging population of nonhuman primates in Asia. The transmission of an exogenous retrovirus, SFV, from macaques ( Macaca fascicularis ) to a human at a monkey temple in Bali, Indonesia, was investigated with molecular and serologic techniques. Antibodies to SFV were detected by Western blotting of serum from 1 of 82 humans tested. SFV DNA was detected by nested polymerase chain reaction (PCR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
144
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 140 publications
(154 citation statements)
references
References 34 publications
5
144
0
1
Order By: Relevance
“…Study sites, selected for their known human-nonhuman primate contact, were located in 4 countries in South and Southeast Asia: Thailand, Indonesia, Nepal, and Bangladesh. The seroprevalence of SFV among the nonhuman primates at these sites has been reported (9,15,17).…”
Section: Study Sites and Populationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Study sites, selected for their known human-nonhuman primate contact, were located in 4 countries in South and Southeast Asia: Thailand, Indonesia, Nepal, and Bangladesh. The seroprevalence of SFV among the nonhuman primates at these sites has been reported (9,15,17).…”
Section: Study Sites and Populationsmentioning
confidence: 99%
“…At-risk populations include veterinarians; laboratory, temple, and zoo workers; pet owners; and bushmeat hunters (16)(17)(18)(19)(20). SFV prevalence in these populations is 1%-6%.…”
Section: Diverse Contexts Of Zoonotic Transmission Of Simian Foamy VImentioning
confidence: 99%
See 2 more Smart Citations
“…Though the local Tourist Board, through GONHS and the Gibraltar Veterinary Clinic, has erected signs that explicitly prohibit visitors from feeding macaques many visitors do offer food to the macaques, and some visitors use food to lure macaques onto their head or shoulders (Fuentes, 2006). Previous work on disease transmission between humans and macaques in Asia suggested that transmission of infectious agents both from human-to-macaque and from macaque-to-human occurred in contexts when humans and free-ranging macaques came into contact (Engel et al, 2002;Jones-Engel et al, 2001,2005a. It is hypothesized that macaque bites and scratches as well as mucosal contact with body fluids can lead to crossspecies transmission.…”
Section: Introductionmentioning
confidence: 99%